MERS-CoV RBD-mRNA vaccine induces potent and broadly neutralizing antibodies with protection against MERS-CoV infection - Wanbo Tai; Jian Zheng; Xiujuan Zhang; Juan Shi; Gang Wang; Xiaoqing Guan; Jiang Zhu; Stanley Perlman; Lanying Du (Virus Research, 2023)
Middle East respiratory syndrome coronavirus (MERS-CoV), a highly pathogenic coronavirus in the same Betacoronavirus genus and Coronaviridae family as SARS-CoV-2, continues to post a threat to human health. Mortality remains high; therefore, there is a need to develop effective vaccines to prevent MERS-CoV infection. The receptor-binding domain (RBD) within the MERS-CoV spike (S) protein is a critical vaccine target. The latest mRNA technology has enabled rapid development of much-needed vaccines with high efficiency and scalable manufacturing capacity. Here, we designed a mRNA vaccine encoding the RBD of MERS-CoV S protein (RBD-mRNA) and evaluated its immunogenicity and protective efficacy in a mouse model. The data showed that nucleoside-modified RBD-mRNA, but not RBD-mRNA lacking the nucleoside modification, was stable and elicited broadly and durable neutralizing antibody and cellular immune responses, which neutralized the original strain and multiple MERS-CoV variants. Among all immunization routes tested, the intradermal route was appropriate for this RBD-mRNA to induce strong B-cell responses and the highest neutralizing antibody titers. Importantly, injection of nucleoside-modified RBD-mRNA through the intradermal route protected immunized mice against challenge with MERS-CoV. This protection correlated with serum neutralizing antibody titers. Overall, we have developed an effective MERS-CoV RBD-based mRNA vaccine (with potential for further development) that prevents infection by divergent strains of MERS-CoV.